2022
DOI: 10.1007/s12672-022-00520-2
|View full text |Cite
|
Sign up to set email alerts
|

Elevated LINC00894 relieves the oncogenic properties of thyroid cancer cell by sponging let-7e-5p to promote TIA-1 expression

Abstract: LINC00894 plays an important role in cancer cell proliferation and invasion in breast and kidney cancer. However, its role in thyroid cancer proliferation and metastasis remains unclear. In this study, data on LINC00894 expression in thyroid cancer tissues were obtained from GEPIA2. miRNA expression in thyroid cancer tissues was obtained from starBase 3.0 and OncomiR. Cell proliferation was evaluated using CCK-8, and Transwell chambers were used for the migration and invasion assays. LINC00894 and let-7e-5p ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Currently, LINC00894, LINC01426, PVT1, and DUXAP8 have been reported to be related to oncogenesis and development. LINC00894 enhances cell proliferation and invasion by binding with miR-429 to mediate ZEB1 expression in breast cancer ( Meng, Shao & Feng, 2021 ); what’s more, in thyroid cancer, its increased expression reduces the oncogenic properties by sponging let-7e−5p to promote TIA-1 expression ( Chen et al, 2022a ). LINC01426 modulates CTBP1/miR-423-5p/FOXM1 axis via interacting with IGF2BP1 to aggravate ccRCC progression ( Jiang et al, 2021b ), it also aggravates the malignant progression through miR-661/Mdm2 axis in glioma ( Shu et al, 2022 ), it serves as a prognostic indicator in lung adenocarcinoma by triggering growth and metastasis ( Deng et al, 2022 ), what’s more, in a recently reported study on ferroptosis-related lncRNAs of glioma, LINC01426 was identified to be related to ferroptosis, its knockdown could significantly increase in the Fe 2+ levels and the erastin-induced ROS levels in glioma cells ( Huang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, LINC00894, LINC01426, PVT1, and DUXAP8 have been reported to be related to oncogenesis and development. LINC00894 enhances cell proliferation and invasion by binding with miR-429 to mediate ZEB1 expression in breast cancer ( Meng, Shao & Feng, 2021 ); what’s more, in thyroid cancer, its increased expression reduces the oncogenic properties by sponging let-7e−5p to promote TIA-1 expression ( Chen et al, 2022a ). LINC01426 modulates CTBP1/miR-423-5p/FOXM1 axis via interacting with IGF2BP1 to aggravate ccRCC progression ( Jiang et al, 2021b ), it also aggravates the malignant progression through miR-661/Mdm2 axis in glioma ( Shu et al, 2022 ), it serves as a prognostic indicator in lung adenocarcinoma by triggering growth and metastasis ( Deng et al, 2022 ), what’s more, in a recently reported study on ferroptosis-related lncRNAs of glioma, LINC01426 was identified to be related to ferroptosis, its knockdown could significantly increase in the Fe 2+ levels and the erastin-induced ROS levels in glioma cells ( Huang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the results of our study. LINC00893 [ 37 ], LINC00894 [ 38 ], and RAMP2-AS1 [ 39 ] are protective factors for colon, thyroid, and breast cancer, respectively. Interestingly, RAMP2-AS1, LINC00893, and LINC00894 are also downregulated in our study model.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, LINC00894 enhances breast cancer cell proliferation and invasion by competitive binding with miR-429 [18]. Nevertheless, studies on thyroid cancer have found that up-regulation of LINC00894 can inhibit tumor cell activity [25]. LINC00894 has not yet been evaluated for its clinical signi cance and function in lymph node metastatic PTC.…”
Section: Discussionmentioning
confidence: 99%
“…The following constructs were procured from RiboBio Co. (Guangzhou, China): pcDNA empty vector, pcDNA-LINC00894, pcDNA-METTL3, pcDNA-YTHDC2, siRNA normal control (SI-NC), and siRNAs targeting LINC00894 (SI-LINC00894). The process of transfection was carried out utilizing either Lipofectamine 2000 (Invitrogen, Carlsbad, CA, USA) or X-tremeGENE transfection reagent (Thermo Fisher Scienti c, USA) following the protocols [25].…”
Section: Cell Transfectionmentioning
confidence: 99%